THE EFFECT OF INTELLECTUAL CAPITAL ON SUSTAINABLE GROWTH MODERATED BY THE GREEN INNOVATION STRATEGY - Medeleen Florencia Kawilarang; Fransiskus E. Daromes; Paulus Tangke (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
This research investigates the effect of intellectual capital on sustainable growth and investigates the moderating role of green innovation strategy in the relationship between intellectual capital and sustainable growth. This research collected 20 companies based on purposive sampling of all non-financial companies on the Indonesia Stock Exchange (IDX) period 2017-2020. The results show that intellectual capital has a negative and significant effect on sustainable growth. The findings also show that green innovation strategy is able to moderate the relationship between intellectual capital and sustainable growth. This research recommends positive values ​​in the green innovation strategy to control intellectual capital in order not to threaten the company's sustainability.